Rehabilitation for Gang-Affiliated, Male, African American Juvenile Delinquents - Berger, Batsheva (2019)
Many social workers are unaware of their responsibilities related to African American, male, juvenile delinquents who have gang affiliation. Punishment by detention is detrimental to these youth because detention perpetuates criminal careers and does not rehabilitate juvenile offenders. The purpose of this action research study was to determine how social workers understood their role in the rehabilitation of gang-affiliated, African American, male juvenile delinquents. Differential association theory was used as the conceptual framework to understand the detriment of youth being incarcerated without rehabilitation. One focus group of 5 social workers was formed using purposive sampling of social workers who worked with the juvenile delinquent population in different settings. Manual transcription, hand coding, and thematic analysis were used to analyze the data. Participants explained why social workers see the population of African American, male, juvenile delinquents with gang involvement as vulnerable, reasons for gang affiliation, barriers to treatment, and how to engage this population. Findings include strategies to promote positivity within urban environments, foster a sense community in these areas, and engage clients. Recommendations were made to advocate for policy change, incorporate the arts into intervention, and to create urban beautification programs. Findings and recommendations from this study might bring about social change by providing insight into how social workers understand their role in the rehabilitation of the population of African American, male, juvenile delinquents with gang involvement and what can be done to enhance the social work involvement